Faktor yang Berhubungan dengan Kejadian Gizi Kurang Pada Balita di Desa Sidomulyo Kecamatan Pulobandring - Debby Pratiwi; Marlina Marlina (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Introduction; Nutritional status is the state of the human body as a result of food consumption and the use of nutrients. Good human nutritional status is influenced by two main things, namely food consumption and the state of health of the body or infection. Malnutrition can result in failure to grow and develop, decreased endurance, lead to loss of healthy life of toddlers, as well as more serious impacts are the onset of disability, high rates of pain and acceleration of death. Purpose; to find out the factors associated with the incidence of malnutrition in toddlers in Sidomulyo Village Pulobandring Subdistrict. Methods; This research uses methods that are analytical surveys with a cross sectional approach. Sampling technique using accidental sampling method, with the number of samples as many as 32 toddlers in Sidomulyo Village Pulobandring Subdistrict. The data was analyzed using Univariate and Bivariate using the chi square test. Results; Studies using the chisquare test showed a relationship between knowledge variables and the incidence of undernutrition (p= 0.015 < 0.05 respondents to trimesters II and III), family income with the incidence of undernutrition (p = 0.010 <.05), and jobs with less nutritional events (p = 0.001 < 0.05). Conclusions; In this study, there is a relationship between knowledge, family income, and work and the incidence of malnutrition in Sidomulyo Village pulobandring district in 2021. It is expected that health workers further improve health promotion as their role to achieve a goal that is to improve the health of mothers and children.